2005
DOI: 10.1254/jphs.fp0040404
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor Nrf2 Regulates Promoter Activity of Mouse Aldose Reductase (AKR1B3) Gene

Abstract: Abstract. Transcription factor Nrf2 regulates gene expression of drug metabolizing enzymes such as glutathione S-transferase via the antioxidant response element, ARE. Aldose reductase (AR), a member of the aldo-keto reductase (AKR) superfamily, metabolizes various endogenous and exogenous aldehydes. The AR gene 5'-flanking region contains a multiple stress response region (MSRR) composed of two putative AREs (ARE1 and ARE2), an AP1 site, and a tonicity response element (TonE). As this region is highly conserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(29 citation statements)
references
References 37 publications
1
28
0
Order By: Relevance
“…Recently, we also observed increased expression of an anti-oxidative enzyme, glutathione peroxidase-3, in the cardiac ventricles of STZ-induced diabetic mice under the same experimental conditions (45). As expression of the AR gene is regulated by the cellular redox state via the transcription factor Nrf2 (25,46,47), the level of AR mRNA may be down-regulated by transient increase in GSH along with augmented activity of anti-oxidative enzymes at the early stage of hyperglycemia.…”
Section: Discussionmentioning
confidence: 79%
“…Recently, we also observed increased expression of an anti-oxidative enzyme, glutathione peroxidase-3, in the cardiac ventricles of STZ-induced diabetic mice under the same experimental conditions (45). As expression of the AR gene is regulated by the cellular redox state via the transcription factor Nrf2 (25,46,47), the level of AR mRNA may be down-regulated by transient increase in GSH along with augmented activity of anti-oxidative enzymes at the early stage of hyperglycemia.…”
Section: Discussionmentioning
confidence: 79%
“…In detailed studies in the murine aldose reductase Akr1b3, two adjacent AREs and an AP-1 site were required for maximal response to cotransfected Nrf2 (Nishinaka and Yabe-Nishimura, 2005). Potential AREs were also identified by sequence analysis in the proximal promoter region of Akr7a3, but they were not characterized (Ellis et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Aldose reductase is known as a target gene of Nrf2. 28,29) However, it seems unlikely that aldose reductase is induced by EPS because our previous study indicated that the reductase activity in Schwann cells was decreased by 30-50% after treatment with 10-100 µM EPS. 10) In addition, these findings suggest that the inhibition of aldose reductase does not contribute to the ability of EPS to increase HO-1 levels by activating Nrf2.…”
Section: )mentioning
confidence: 99%